Analisis Kesulitan Belajar Matematika pada Materi Jarak, Waktu dan Kecepatan pada Siswa Kelas V SDN 24 Banyuasin 1 - Febrina, Melly; Hermansyah, Bambang; Marleni, Marleni (Institut Teknologi Pendidikan Indonesia, 2022)
The formulation of the problem in this study is first, what are the factors that cause difficultiesin learning mathematics in the material of distance, time and speed in fifth grade students ofSDN 24 Banyuasin I, second, how to overcome difficulties in learning mathematics on distance, time and speed materials in fifth grade students of SDN 24 Banyuasin I. The purpose of this study was to determine the causes and ways of overcoming the difficulties of learning mathematics on the subject of distance, time and speed in fifth grade students of SDN 24 Banyuasin I. This research method is a descriptive qualitative method. Data collection techniques used are observation, tests, interviews and documentation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results of this study are (1) There are three difficulties experienced by students when learning mathematics on the subject of distance, time and speed, namely difficulty understanding concepts, difficulties in counting and difficulties in language and writing. (2) The factors that cause learning difficulties in the material of distance, time and speed of classV students at SDN 24 Banyuasin I are internal and external factors. Internal factors such as interests, attitudes, motivation, intelligence and health disorders, while external factors such as family factors. (3) The way to overcome the difficulties of learning mathematics in the matter of distance, time and speed is that the teacher approaches students, providing remedial for students who get scores below the KKM.